Empowering Lives through Football: A Narrative Review of the Homeless World Cup as a Sport-Based Intervention for Social Inclusion - Castyana, Billy; Rahayu, Tandiyo (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Homelessness is a multidimensional form of social exclusion rooted in trauma, stigma, and structural inequality, requiring interventions that extend beyond housing provision alone. Sport-based initiatives have emerged as complementary approaches to psychosocial engagement, yet their mechanisms and sustainability remain underexplored. This review offers a mechanism-oriented synthesis of the Homeless World Cup (HWC) as a global sport-based intervention for social inclusion, advancing a novel conceptual framing that positions the HWC as a psychosocial catalyst rather than a standalone solution. Using a narrative systematic review approach, peer-reviewed studies on the HWC, street soccer, homelessness, trauma-informed care, and public health were analyzed thematically. Findings indicate that participation fosters psychosocial empowerment, social capital development, identity reconstruction, and service engagement, primarily through recognition, belonging, and relational connection. However, outcomes are highly conditional upon institutional scaffolding, housing stability, and integrated health and social services. The discussion highlights the necessity of trauma-informed delivery and structural support, contributing a critical lens to sport-for-development scholarship and informing policy and practice for sustainable social inclusion.